2010
DOI: 10.1098/rstb.2010.0125
|View full text |Cite
|
Sign up to set email alerts
|

The annual cycles of phytoplankton biomass

Abstract: Terrestrial plants are powerful climate sentinels because their annual cycles of growth, reproduction and senescence are finely tuned to the annual climate cycle having a period of one year. Consistency in the seasonal phasing of terrestrial plant activity provides a relatively low-noise background from which phenological shifts can be detected and attributed to climate change. Here, we ask whether phytoplankton biomass also fluctuates over a consistent annual cycle in lake, estuarine -coastal and ocean ecosys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
170
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 254 publications
(185 citation statements)
references
References 79 publications
9
170
1
3
Order By: Relevance
“…This suggests that either the climatic changes were not strong enough to induce a trend in lake water, except for summer, or that the effect of these variables was confounded by catchment-specific factors. An analysis of 125 freshwater and marine phytoplankton time series demonstrated that climate-driven phytoplankton biomass cycles were heavily obscured by other drivers of population variability, indicating the difficulty of detecting climate-driven trends in plankton communities [58]. However, a long-term warming trend has been documented for both North American [17,18] and European [19,20] deep lakes in investigations covering a longer time period than in our study.…”
Section: Discussioncontrasting
confidence: 59%
“…This suggests that either the climatic changes were not strong enough to induce a trend in lake water, except for summer, or that the effect of these variables was confounded by catchment-specific factors. An analysis of 125 freshwater and marine phytoplankton time series demonstrated that climate-driven phytoplankton biomass cycles were heavily obscured by other drivers of population variability, indicating the difficulty of detecting climate-driven trends in plankton communities [58]. However, a long-term warming trend has been documented for both North American [17,18] and European [19,20] deep lakes in investigations covering a longer time period than in our study.…”
Section: Discussioncontrasting
confidence: 59%
“…Winder and Cloern, 2010;Read et al 2012). Similarly, Lake Heat Flux Analyzer can be used for global scale research by calculating the surface fluxes using the same method, which is essential for cross-site collaboration.…”
Section: Discussionmentioning
confidence: 99%
“…Phytoplankton is very sensitive to environmental changes, and shifts in cyclical behavior are reported to occur because of changes (such as ENSO events), that modify the climate and meteorological forces, at short and long time scales [74]. The decrease of rainfall in 2007-2008 (La Niña) generated a reduction in the freshwater and nutrients inputs and also an increase in the salinity, which could possibly cause deep changes in phytoplankton community composition [75,76].…”
Section: Discussionmentioning
confidence: 99%